Effect of 3-Month Aerobic Dance on Hippocampal Volume and Cognition in Elderly People With Amnestic Mild Cognitive Impairment: A Randomized Controlled Trial - Zhu, Yi; Gao, Yaxin; Guo, Chuan; Qi, Ming; Xiao, Ming; Wu, Han; Ma, Jinhui; Zhong, Qian; Ding, Hongyuan; Zhou, Qiumin; Ali, Nawab; Zhou, Li; et al. (Frontiers in Aging Neuroscience, 2022)
As an intermediate state between normal aging and dementia, mild cognitive impairment (MCI), especially amnestic MCI (aMCI), is a key stage in the prevention and intervention of Alzheimer's disease. Whether dancing could increase the hippocampal volume of seniors with aMCI remains debatable. The aim of the present study was to investigate the influence of aerobic dance on hippocampal volume and cognition after three months' aerobic dance in older adults with aMCI. In this randomized controlled trial, 68 elderly people with aMCI were randomized to either the aerobic dance group or the control group using a 1:1 allocation ratio. Ultimately, 62 of 68 participants completed the study, and the MRI data of 54 participants were included. A specially designed aerobic dance routine was performed by the dance group three times per week for three months, and all participants received monthly health care education after inclusion. MRI with a 3.0 T MRI scanner and cognitive assessments were performed before and after intervention. High-resolution 3D T1-weighted anatomical images were acquired for the analysis of hippocampal volume. A total of 35 participants were randomized into the aerobic dance group and 33 into the control group. A multiple linear regression model was used to detect the association between intervention and the difference of hippocampal volumes as well as the change of cognitive scores at baseline and after three months. The intervention group showed greater right hippocampal volume (β [95% CI]: 0.379 [0.117, 0.488], p = 0.002) and total hippocampal volume (β [95% CI]: 0.344 [0.082, 0.446], p = 0.005) compared to the control group. No significant association of age or gender was found with unilateral or global hippocampal volume. There was a correlation between episodic memory and intervention, as the intervention group showed a higher WMS-RLM score (β [95% CI]: 0.326 [1.005, 6.773], p = 0.009). Furthermore, an increase in age may cause a decrease in MMSE score (β [95% CI]: -0.366 [-0.151, -0.034], p = 0.002). In conclusion, three months of aerobic dance could increase the right and total hippocampal volumes and improve episodic memory in elderly persons with aMCI.